Thermodynamics of Highly Charged Protein Interactions - Walse,Klara (2025)
The primary objective of this master's thesis was to systematically investigate how the net charge and charge distribution of disordered Histone H1.0 peptide variants influence the thermodynamics of their interaction with the fully disordered protein, Prothymosin-alpha (ProTα). This research aimed to provide new insights into the principles governing polyelectrolytic binding between two highly charged, intrinsically disordered proteins. Using Isothermal Titration Calorimetry, the binding affinities and thermodynamic profiles of four different H1 variants, CV+11, CV+21, CV+32, and the globular domain GD+11 were successfully characterized in various ionic strength buffers. A central finding was the strong linear correlation between the net charge of the H1 variants for both the enthalpy change and the binding affinity. These results suggest that the binding is primarily influenced by electrostatic forces, with the increase in charge density likely leading to a greater release of counterions. The identity of these ions also suggests having a large influence on the observed enthalpy change. The ITC data were complemented with 1H- 15N HSQC NMR titrations for the CV+11 and CV+21 variants. The NMR spectra showed similar movements in chemical shifts for both variants, providing complimentary insights into the binding site of the interactions.
Keywords: Intrinsically Disordered Proteins; Polyelectrolytic binding; Isothermal Titration Calorimetry; NMR spectroscopy; Biophysical Chemistry